2013
DOI: 10.1021/ml4002985
|View full text |Cite
|
Sign up to set email alerts
|

Novel Endoperoxide-Based Transmission-Blocking Antimalarials with Liver- and Blood-Schizontocidal Activities

Abstract: In a search for effective compounds against both the blood-and liver-stages of infection by malaria parasites with the ability to block the transmission of the disease to mosquito vectors, a series of hybrid compounds combining either a 1,2,4-trioxane or 1,2,4,5-tetraoxane and 8-aminoquinoline moieties were synthesized and screened for their antimalarial activity. These hybrid compounds showed high potency against both exoerythrocytic and erythrocytic forms of malaria parasites, comparable to representative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…To seek for capable candidates against both the blood‐ and liver‐stages of malaria parasites, three PQ‐ART hybrids 5 (Figure ) were designed, synthesized, and evaluated for their multistage antiplasmodial activities against CQR W2 P falciparum and Plasmodium berghei strains . All hybrids (IC 50 : 5.1‐523 nM) were highly active against both erythrocytic (CQR W2 P falciparum ) and exoerythrocytic ( P berghei ) forms of malaria parasites, and they were comparable to ART (IC 50 : 8.2 nM) against erythrocytic stage of P falciparum , 14 to 647 times more potent than PQ (IC 50 : 3300 and 7500 nM) against erythrocytic stage of P falciparum and exoerythrocytic stage of P berghei .…”
Section: Quinoline‐artemisinin (Or Its Derivatives) Hybrids (Type I)mentioning
confidence: 99%
“…To seek for capable candidates against both the blood‐ and liver‐stages of malaria parasites, three PQ‐ART hybrids 5 (Figure ) were designed, synthesized, and evaluated for their multistage antiplasmodial activities against CQR W2 P falciparum and Plasmodium berghei strains . All hybrids (IC 50 : 5.1‐523 nM) were highly active against both erythrocytic (CQR W2 P falciparum ) and exoerythrocytic ( P berghei ) forms of malaria parasites, and they were comparable to ART (IC 50 : 8.2 nM) against erythrocytic stage of P falciparum , 14 to 647 times more potent than PQ (IC 50 : 3300 and 7500 nM) against erythrocytic stage of P falciparum and exoerythrocytic stage of P berghei .…”
Section: Quinoline‐artemisinin (Or Its Derivatives) Hybrids (Type I)mentioning
confidence: 99%
“…Hybrid molecules capable of hitting more than one molecular target are an attractive alternative to currently approved antimalarial drugs. Thus, two antiplasmodial drugs with different modes of action, primaquine and artemisinin, were combined in hybrids 162e164 [119,120]. Amine and amide covalent bonds between primaquine and artemisinin were achieved according to the procedures presented in Scheme 9.…”
Section: Primaquine-artemisinin Conjugatesmentioning
confidence: 99%
“…A small library of hybrid compounds 165e168 combining 1,2,4,5-tetraoxane (endoperoxide system similar to 1,3,4-trioxane present in artemisinin) and primaquine or other 8aminoquinoline moieties was prepared and screened for the antimalarial activity (Scheme 10) [120,121]. These hybrids showed high potency against both exoerythrocytic and erythrocytic forms of malaria parasites and efficiently blocked the development of the sporogonic cycle in the mosquito vector.…”
Section: Primaquine-artemisinin Conjugatesmentioning
confidence: 99%
“…Miranda et al (18) reported a series of hybrid compounds combining either a 1,2,4-trioxane or 1,2,4,5-tetraoxane and 8-aminoquinoline moieties. The hybrids were synthesized and screened for their antimalarial activity.…”
Section: Advantages Of Hybridsmentioning
confidence: 99%
“…• Nature of the linker unit employed Figure 1 illustrates a detailed classification of hybrids based on the categories listed above, along with an example of a hybrid compound in each category (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%